Prosthetic graft replacement of a large subclavian aneurysm in a child with Loeys–Dietz syndrome: a case report. Issue 5 (23rd August 2020) - Sobh, Mohamed; Voges, Inga; Attmann, Tim; Scheewe, Jens
Abstract: Background: Loeys–Dietz syndrome (LDS) is a genetic connective tissue disorder, which is characterized by rapid development of aortic and peripheral arterial aneurysms. Loeys–Dietz syndrome has some overlapping phenotypic features with other inherited aortopathies such as Marfan syndrome. However, LDS has a more aggressive vascular course with patient morbidity and mortality occurring at an early age. Case summary: We present the rare case of an 11-year-old girl with LDS who underwent valve sparing aortic root replacement at the age of 2.9 years with good results. She had routine follow-up cardiovascular magnetic resonance imaging and was found to have a large aneurysm of the right subclavian artery. After multidisciplinary team discussion, successful surgical resection with prosthetic graft replacement of the right subclavian artery was performed. Discussion: This case illustrates that large aneurysms of aortic branches can already develop in childhood and underlines the need for frequent follow-ups including cross-sectional imaging and multidisciplinary team management.